Meglumine-based supra-amphiphile self-assembled in water as a skin drug delivery system: Influence of unfrozen bound water in the system bioadhesiveness - de Souza, Ana Luiza R. [UNESP]; Fonseca, Mariana [UNESP]; Ferreira, Leonardo Miziara Barboza [UNESP]; Kurokawa, Suzy S.S. [UNESP]; Kiill, Charlene P. [UNESP]; Ferreira, Natália N. [UNESP]; dos Santos Pyrrho, Alexandre; Sarmento, Victor H.V.; Silva, Amélia M.; Gremião, Maria Palmira D. [UNESP]; Ribeiro, Clóvis A. [UNESP] (Elsevier, 2019)
Hexagonal liquid crystals and supramolecular polymers from meglumine-based supra-amphiphiles were developed as drug delivery systems to be applied on the skin. The influence of fatty acid unsaturation on the structure and mechanical properties was evaluated. Moreover, we have investigated the system biocompatibility and how the type of water could influence its bioadhesive properties. Meglumine-oleic acid (MEG-OA) was arranged as hexagonal liquid crystals at 30–70 wt% water content, probably due to its curvature and increased water solubility. Meglumine-stearic acid (MEG-SA) at 10–80 wt% water content self-assembled as a lamellar polymeric network, which can be explained by the low mobility of MEG-SA in water due to hydrophobic interactions between fatty acid chains and H-bonds between meglumine and water molecules. Both systems have shown suitable mechanical parameters and biocompatibility, making them potential candidates to encapsulate therapeutic molecules for skin delivery. Moreover, a strong positive correlation between the amount of unfrozen bound water in meglumine-based systems and the bioadhesion properties was observed. This work shows that a better understanding of the physicochemical properties of a drug delivery system is extremely important for the correlation with the desired biological response and, thus, improve the product performance for biomedical applications.
Keywords: Bioadhesion; Hexagonal liquid crystals; Meglumine-based systems; Supra-amphiphiles; Supramolecular polymers; Unfrozen bound water